A Pure and Indistinguishable Single‐Photon Source at Telecommunication Wavelength. Issue 5 (25th March 2022) - Da Lio, Beatrice; Faurby, Carlos; Zhou, Xiaoyan; Chan, Ming Lai; Uppu, Ravitej; Thyrrestrup, Henri; Scholz, Sven; Wieck, Andreas D.; Ludwig, Arne; Lodahl, Peter; Midolo, Leonardo
Abstract: On‐demand single‐photon sources emitting pure and indistinguishable photons at the telecommunication wavelength are critical assets toward the deployment of fiber‐based quantum networks. Indeed, single photons may serve as flying qubits, allowing communication of quantum information over long distances. Self‐assembled InAs quantum dots embedded in GaAs constitute an excellent nearly deterministic source of high‐quality single photons, but the vast majority of sources operate in the 900–950 nm wavelength range, precluding their adoption in a quantum network. A quantum frequency conversion scheme is presented here for converting single photons from quantum dots to the telecommunication C band, around 1550 nm, achieving 40.8% end‐to‐end efficiency, while maintaining both high purity and a high degree of indistinguishability during conversion with measured values of g ( 2 ) ( 0 ) = 2.4 % g^(2)(0)=2.4% and V (corr) = 94.8 % V^(corr)=94.8%, respectively. Abstract : On‐demand single‐photon sources emitting pure and indistinguishable photons at the telecommunication wavelength are critical assets toward the deployment of fiber‐based quantum networks. This work presents a quantum frequency conversion scheme for converting single photons from InAs/GaAs quantum dots to the telecommunication C band achieving 40.8% end‐to‐end efficiency, while maintaining high purity ( g ( 2 ) ( 0 ) = 2.4 % g^(2)(0)=2.4% ) and high indistinguishability ( V (corr) = 94.8 % V^(corr)=94.8% ).